Working status is not related to exclusive breastfeeding - Agung Nugroho (International Journal of Health Science and Technology, 2022)
Breast Milk is known as the best food for babies and contains many nutritious substances. Many factors influenced successful breastfeeding, especially for working mothers. This study is intended to explore the relationship between mothers' employment status and breastfeeding status using a cross-sectional design that utilizes secondary data collected from the implementation of the "Sleman Health Demographic Surveillance System". Other variables collected were education attainment and living location. Data used in this study was 297 by direct interviews with mothers of infants/toddlers or their caregivers. Chi-square analysis was used to determine the relationship between employment status and breastfeeding with a significance level of 95%. The percentage of basic education attainment in the sample did not differ from the national figure, while women who can complete high school and college education are higher than the national figure. More than half of the respondents are not working. No relationship was found in the analysis of relationships between mothers' employment status and breastfeeding status (p-value 0.05).